Association of plasma metabolites with treatment response after intravitreal anti-vascular endothelial growth factor injections in treatment-naïve neovascular age-related macular degeneration - Inês Laíns; Deeba Husain; Joan W Miller; Ivana K Kim; John B Miller; Demetrios G Vavvas; Raviv Katz; Liming Liang; Jessica Lasky-Su; Archana Nigalye; Kevin M Mendez; David Wu; et al. (BMJ Open Ophthalmology)
Background/aims To investigate the association between plasma metabolomic profiles and treatment response after intravitreal anti-vascular endothelial growth factor (VEGF) injections in treatment-naïve neovascular age-related macular degeneration (nAMD).Methods This is part of a prospective longitudinal study that included patients with treatment-naïve nAMD who have undergone three loading intravitreal anti-VEGF injections. All patients underwent ophthalmological examinations including spectral domain optical coherence tomography (SD OCT). Fasting blood samples were collected at the time of study enrolment (not to first anti-VEGF injection) and metabolomic profiling was conducted using ultra-performance liquid chromatography–mass spectrometry. Treatment response was defined as no evidence of any subretinal and intraretinal fluid on SD OCT 4–6 weeks after the third injection. Multilevel mixed-effects linear modelling was used to assess associations between plasma metabolites and treatment response. Multiple comparisons were accounted for using the effective number of tests to explain 80% of the variance (ENT80), with a p value threshold of 0.0017.Results We included 131 eyes of 101 patients, and 69 patients (68.3%) were female. 51 eyes (38.9%) were treatment responders. Taurodeoxycholate (TDCA) was the only plasma metabolite significantly associated with treatment response (β=1.6, ENT80=0.001).Conclusion In our study, TDCA was the most significant plasma metabolite associated with treatment response after three-loading dose of anti-VEGF therapy in patients with nAMD. Bile acids may have a beneficial impact on treatment response in nAMD through their neuroprotective property. Plasma metabolites may be used as biomarkers to predict responses to initial anti-VEGF therapy in patients with nAMD, providing a more individualised treatment plan.